21 ASSESSING SARCOPENIA, FRAILTY AND MALNUTRITION IN COMMUNITY-DWELLING DEPENDANT OLDER ADULTS – A HOME-BASED STUDY WITH AN UNDERREPRESENTED GROUP IN RESEARCH. (25th October 2022) - Swan, L; Martin, N; Warters, A; O'Sullivan, M
Abstract: Background: Sarcopenia, frailty, and malnutrition are known determinants of adverse health outcomes. Adults of advanced age, with functional dependency, socioeconomic disadvantage, or a need for home care, are expected to be at high risk of these conditions yet are likely to be underrepresented in research. We aimed to examine the feasibility and preliminary outcomes of conducting home-based assessments in this group. Methods: Home-based health assessments were conducted among older adults (n= 31), in receipt of state-funded home care. Assessments included probable sarcopenia [hand-grip strength (HGS), chair rise-test and SARC-F case-finding tool] in line with the European Working Group on Sarcopenia in Older People 2 (EWGSOP2) guidelines, the Mini Nutritional Assessment (MNA), and the Clinical Frailty Scale (CFS). Results: The study group was of mean age 83.2 ± 8.2 years, 74% female, 23% lived in socioeconomically disadvantaged areas, had comorbidities (n=30, 97%) and low physical activity (71%). We found that almost all met the criteria for probable sarcopenia (94%, 29/31), most were frail or vulnerable by CFA (97%, 30/31), and over a quarter were at risk of malnutrition (26%, n=8). In all participants, it was feasible to assess sarcopenia (by HGS and SARC-F, but not chair rise test), malnutrition (MNA), and frailty (CFS). Notably, in-home assessments required additional time, the adaptation of assessment tools, responsibility to address issues arising, including signposting to health services (36%, n=11), and navigating complex psychosocial environments; the latter was commonly observed in areas of socioeconomic disadvantage. Conclusion: Assessing sarcopenia, frailty, and malnutrition in community-dwelling dependant older adults in-home was feasible, once potential challenges were considered. Moreover, our findings suggest that most participants were at risk of both sarcopenia and frailty, and over a quarter were at risk of malnutrition. This highlights a need for further research and proactive evidence-based multi-modal community interventions to support ageing in place.